Global Competence and Sustainable Practices Among Senior Secondary Students in Patna - Rane, Ravi; Mulik, Pooja (Journal of Educational Research and Policies, 2026)
This study examines global competence and sustainable practices among senior secondary students in Patna, India. It assesses students’ awareness of global challenges, such as environmental sustainability, social equity, and cultural understanding, and explores how these issues are incorporated into their daily lives. Global Competence and Sustainable Practices are need of the hour. It is imperative to teach our next generation to respect Mother Nature. With this research paper the researcher wants to analyse the gap between the knowledge and practice of senior secondary students. This qualitative research explores the global competence and sustainable practices of senior secondary students in Patna, India. Utilizing semi - structured interviews and focus group discussions, the study investigates students’ awareness, attitudes, and behaviors regarding global challenges and sustainability. Findings indicate a growing awareness of global issues, yet gaps persist in practical engagement with sustainable practices. Recommendations for educational strategies aimed at enhancing global competence and promoting sustainability are provided. The study emphasizes the need for a more integrated educational approach to enhance global competencies and promote responsible, sustainable behaviors among students, fostering greater engagement with global citizenship and sustainability.